Impact of Immigration Reform and Control Act Gender Differences in the Labor Market: An analysis of the impact of forgiveness provision on labor market outcomes for the legalized population (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This paper tests whether forgiveness, a provision of the Immigration Reform and Control Act (IRCA), affected the labor market outcomes of the legalized population. Using the Legalized Population Survey (LPS) and the National Longitudinal study of Youth from 1987-1992, a quasi-experimental framework is developed to review the differential impact of forgiveness on the allowed population relative to a comparison grouping. After the implementation of the general pardon program, employment fell and unemployment rose for lately legalized men relative to the comparison group of already legal Indian residents. For women, employment also fell and transitions out of the labor force increased between the newly legalized populations. Increasing returns to skill, as ability, only played a significant job in explanation the employment of newly legalized women. Finally, newly legalized men and women enjoyed higher wage development rates than their working native counterparts, possibly owing to their moderately increasing returns to Indian educational achievement over this stage.